2005
DOI: 10.1111/j.1471-4159.2005.03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Globular amyloid β‐peptide1−42 oligomer − a homogenous and stable neuropathological protein in Alzheimer's disease

Abstract: Amyloid b-peptide (Ab) 1)42 oligomers have recently been discussed as intermediate toxic species in Alzheimer's disease (AD) pathology. Here we describe a new and highly stable Ab 1)42 oligomer species which can easily be prepared in vitro and is present in the brains of patients with AD and Ab 1)42 -overproducing transgenic mice. Physicochemical characterization reveals a pure, highly water-soluble globular 60-kDa oligomer which we named 'Ab 1)42 globulomer'. Our data indicate that Ab 1)42 globulomer is a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
619
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(663 citation statements)
references
References 40 publications
41
619
3
Order By: Relevance
“…However, when also considering that disordered regions may remain in the ∼100-kDa β-sheet oligomers, these should contain at least 12 monomer subunits. Hence, a dodecamer stoichiometry of toxic Aβ oligomers that has been favored in other research (4,(28)(29)(30) is consistent with our data.…”
Section: Discussionsupporting
confidence: 82%
“…However, when also considering that disordered regions may remain in the ∼100-kDa β-sheet oligomers, these should contain at least 12 monomer subunits. Hence, a dodecamer stoichiometry of toxic Aβ oligomers that has been favored in other research (4,(28)(29)(30) is consistent with our data.…”
Section: Discussionsupporting
confidence: 82%
“…Addition of four scFv's blocked any Ab42-induced toxicity at the 0 and 21 h time points. These results are consistent with many previous studies that identified the soluble oligomeric Ab42 forms as the toxic species responsible for neuronal cell death and the inhibition of toxicity by antibodies [3][4][5][6]. Although there are no Ab42 oligomers present in the samples of Ab42 alone and Ab42 with scFv's at 0 time point (Fig.…”
Section: Scfv's Block Cytotoxicity Of Ab Oligomerssupporting
confidence: 93%
“…Aβ 1−42 SDSderived oligomers were used for the experiments described in this report. Aβ 1−42 SDS-derived oligomers (globulomers) were prepared according to the general protocol described in, 21 but with some modifications. Aβ 1−42 monomer from Anaspec was redissolved in DMSO (1.0 mg/44 μL/), and sonicated for 5 min.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%